The Role of PTSD in Bi-directional Intimate Partner Violence in Military and Veteran Populations: A Research Review - Misca, Gabriela; Forgey, Mary Ann (Frontiers in Psychology, 2017)
Evidence supporting the higher prevalence of PTSD linked to combat-related trauma in military personnel and veteran populations is well-established. Consequently, much research has explored the effects that combat related trauma and the subsequent PTSD may have on different aspects of relationship functioning and adjustment. In particular, PTSD in military and veterans has been linked with perpetrating intimate partner violence (IPV). New research and theoretical perspectives suggest that in order to respond effectively to IPV, a more accurate understanding of the direction of the violence experienced within each relationship is critical. In both civilian and military populations, research that has examined the direction of IPV’s, bi-directional violence have been found to be highly prevalent. Evidence is also emerging as to how these bi-directional violence differ in relation to severity, motivation, physical and psychological consequences and risk factors. Of particular importance within military IPV research is the need to deepen understanding about the role of PTSD in bi-directional IPV not only as a risk factor for perpetration but also as a vulnerability risk factor for victimization, as findings from recent research suggest. This paper provides a timely, critical review of emergent literature to disentangle what is known about bi-directional IPV patterns in military and veteran populations and the roles that military or veterans’ PTSD may play within these patterns. Although this review aimed to identify global research on the topic, the majority of research meeting the inclusion criteria was from US, with only one study identified from outside, from Canada. Strengths and limitations in the extant research are identified. Directions for future research are proposed with a particular focus on the kinds of instruments and designs needed to better capture the complex interplay of PTSD and bi-directional IPV in military populations and further the development of effective interventions.